BENDUNGAN WATERVANG: PENGARUH DAN PERKEMBANGAN NYA SAMPAI SAAT INI - rahmawan, titet fauzi (Siddhayatra, 2018)
Watervang dam is built by stemming the Kelingi River which divides Lubuk Linggau City.The dam is built for the purpose of developing agriculture and the economy after ethicalpolitics. This paper looks at how the influence of the Watervang Dam on Lubuk LinggauCity and its development to date. To see the influence of the survey and the study of dam librariesin the present. This dam consists of dam components, suspension bridges, water reservoirs,water gates, sedimentary buildings, warehouses, rain gauges, and tourism supportbuildings. The influence of the watervang dam in general to Lubuk Linggau City is the formationof the city's supporting area. This city's economic support area is one of the largestrice producers in South Sumatra until now.